Energy-absorbing metal ceramic composite particle accumulation and preparation method thereof

By filling metal particles in the superelastic ceramic particles, forming energy-absorbing metal cermet composite particles accumulation, the problems of size-brittleness contradiction, phase change threshold and low energy dissipation density in the stacking of superelastic ceramic particles are solved, and higher compressive strength and energy dissipation density are achieved, and the preparation process is energy-saving and time-saving.

CN119663043AActive Publication Date: 2025-03-21SHANGHAI JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411866971.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

There are problems of size-brittleness contradictions in the accumulation of superelastic ceramic particles, the existence of phase change thresholds, and the low energy dissipation density.

Method used

A composite particle accumulation of energy-absorbing metal cermet is adopted to fill metal particles in the superelastic ceramic particles to form composite particle accumulation. Using the deformability of the metal particles and the structural framework of the ceramic particles, a higher level of reversible phase transformation of the superelastic ceramic is achieved, and the compressive strength and energy dissipation density are improved.

Benefits of technology

A higher level of reversible phase transformation of superelastic ceramics is achieved, which improves compressive strength and energy dissipation density, enhances cycle stability, and saves energy and time-saving the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663043A_ABST
    Figure CN119663043A_ABST
Patent Text Reader

Abstract

The invention relates to an energy-absorbing metal ceramic composite particle stack and a preparation method thereof, the composite particle stack comprises superelastic ceramic particles CexZr (1-x) O2 and metal particles M, and the component expression is y% M (at) (100-y)% CexZr (1-x) O2, wherein the particle size of the superelastic ceramic particles is 1-10 [mu] m; the metal particles M are one of Cu, Al, Ti, Ni or alloy, and the particle size is 0.5-5 [mu] m; in the component expression, x is an atom molar ratio, and x is more than or equal to 0.14 and less than or equal to 0.18; y is the mass ratio, and 5 < = y < = 45. The metal ceramic composite particle stack is formed by dispersing superelastic ceramic particles and metal particles through a solvent, drying, stacking and pre-pressing the superelastic ceramic particles and the metal particles. The metal ceramic composite particle accumulation provided by the invention has excellent compressive strength, energy dissipation density and cycling stability, the preparation process is energy-saving and time-saving, and the metal ceramic composite particle accumulation has wide application in the fields of damping, shock absorption, energy absorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite particle stacking and energy dissipation, and specifically, to a metal-ceramic composite particle stacking and a preparation method thereof, which has excellent energy dissipation density and cycle stability, and the preparation process is energy-saving and time-saving, and has wide applications in damping, shock absorption, energy absorption and other fields. Background Art

[0002] Superelastic ceramics are smart materials that can undergo a reversible martensitic phase transformation in response to temperature and / or stress field stimulation, and are widely used in the fields of shape memory, robotics, microelectromechanical systems (MEMS), etc. However, these superelastic ceramics in polycrystalline form are limited by intrinsic grain boundary brittleness and significant phase transformation-induced lattice strain (~5-10%, far exceeding the elastic limit of about 1%), which restricts their large-scale applications (Nature 322, 234-236, 1986).

[0003] In the past decade, researchers have improved the macroscopic brittleness of this type of ceramics to a certain extent through miniaturization (Science 341, 1505-1508, 2013), lattice engineering (Nature 610, 491-495, 2022), configuration (Sci. Adv. 4, eaas8925, 2018), and composite (Nat. Commun. 14, 7103, 2023). For example, Yu Hang and other scholars proposed a strategy for the stacking of superelastic ceramic particles (Acta Mater. 132, 455-466, 2017; Acta Mater. 168, 362-375, 2019), combined with in-situ neutron diffraction experiments and simulations, revealing the phase change mechanism and energy dissipation principle of superelastic ceramic particle stacking, and achieving good cyclic stability and energy dissipation density. This type of superelastic particle stacking can not only convert external kinetic energy into internal energy through friction between particles, but also achieve high energy dissipation and reuse through stress-induced reversible phase change of particles. At the same time, in this type of superelastic ceramic particle stacking, the brittle fracture of particles will further release strain energy and obtain a better superelastic effect.

[0004] Nevertheless, the above-mentioned superelastic ceramic particle stacking also has problems such as insufficient stress transmission, a threshold value of phase transition variable, and low energy dissipation density. In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the "size-brittleness" contradiction of superelastic ceramics and the problems of low phase change threshold and energy dissipation density in the superelastic ceramic particle stacking, the first purpose of the present invention is to provide an energy-absorbing metal-ceramic composite particle stacking that can induce a higher level of reversible phase change of superelastic ceramics, with high compressive strength, energy dissipation density and good cyclic stability.

[0006] The second purpose of the present invention is to provide a method for preparing energy-absorbing metal-ceramic composite particle accumulation. Under the premise of ensuring the integrity of the three-dimensional network force chain and the monomer performance of the superelastic ceramic, this method fills the three-dimensional network pores of the ceramic with metal to fully transfer stress and deformation, and has the advantages of energy-saving and time-saving preparation process and high output.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] The present invention provides an energy-absorbing metal-ceramic composite particle stack, wherein the composite particle stack comprises superelastic ceramic particles Ce x Zr 1-x O2 and metal particles M, the composition expression is: y%M@(100-y)%Ce x Zr 1-x O2;

[0009] The superelastic ceramic has a particle size of 1-10 μm and performs the functions of structural framework and energy dissipation;

[0010] The metal particles M are at least one of Cu, Al, Ti, Ni metal powder or alloy powder thereof, with a particle size of 0.5-5 μm, in a discontinuous particle shape, and having the functions of being deformable and filling pores;

[0011] In the composition expression, x is the atomic molar ratio, 0.14≤x≤0.18; y is the mass percentage, 5≤y≤45, that is, the mass content of the metal particles M is 5-45%.

[0012] As a preferred solution, in the composition expression, 5≤y≤25, that is, the mass content of the metal particles M is 5-25%.

[0013] As a preferred embodiment, the superelastic ceramic particles Ce x Zr 1-x The particle size ratio of O2 to metal particles M is 2-5:1.

[0014] As a preferred solution, the metal particles M are at least one of Cu, Ti, Ni metal powder or alloy powder thereof; when the metal particles M are Cu, Ti, Ni, the energy dissipation density may be more significantly improved.

[0015] As a preferred embodiment, the compressive strength of the composite particle stack is above 0.6 GPa, more preferably above 0.8 GPa.

[0016] As a preferred solution, after 50 cycles of the composite particle stacking, the energy dissipation density is 1.8 J / cm 3 More preferably 2.5 J / cm 3 above.

[0017] As a preferred solution, when the metal particle M is Cu, in the composition expression, 5≤y≤25, the superelastic ceramic particle Ce x Zr 1-x When the particle size ratio of O2 to metal particles M is 2-5:1, the energy dissipation density of the prepared metal-ceramic composite particles can reach 2.5 J / cm after 50 cycles. 3 above;

[0018] When the metal particle M is Al, in the composition expression, 5≤y≤15, the superelastic ceramic particle Ce x Zr 1-x When the particle size ratio of O2 to metal particles M is 2-5:1, the energy dissipation density of the prepared metal-ceramic composite particles can reach 2.6 J / cm after 50 cycles. 3 above;

[0019] When the metal particle M is Ni, in the composition expression, 5≤y≤20, the superelastic ceramic particle Ce x Zr 1-x When the particle size ratio of O2 to metal particles M is 2-5:1, the energy dissipation density of the prepared metal-ceramic composite particles can reach 3.1 J / cm after 50 cycles. 3 The present invention also provides a method for preparing energy-absorbing metal-ceramic composite particle stacking, comprising the following steps:

[0020] A1. Solvent dispersion: weigh the superelastic ceramic particles Ce x Zr 1-x O2 and metal particles M are added to a sufficient amount of solvent and mixed thoroughly for 6-18h;

[0021] A2, drying: placing the mixed slurry obtained in step A1 in a ventilated environment at 50-100° C. and drying for 6-12 hours to obtain metal-ceramic composite particles;

[0022] A3. Stacking pre-pressing: placing the metal-ceramic composite particles in a mold and pre-pressing them at 100-200 MPa to obtain a stack of metal-ceramic composite particles.

[0023] As a preferred embodiment, in step A1, the solvent is one of ethanol, propanol, isopropanol, acetone, butanone, or a mixture of several of them.

[0024] As a preferred embodiment, in step A1, the rotation speed used during the mixing does not exceed 150 rpm.

[0025] As a preferred solution, in step A1, a ball mill or a powder mixer is used for mixing.

[0026] In the energy-absorbing metal-ceramic composite particle stacking described in the present invention, the superelastic ceramic assumes the main structural skeleton and energy dissipation functions; by regulating the reasonable metal content, the pores in the structural skeleton of the superelastic ceramic can be effectively filled, and the synergistic deformation can be achieved during the loading process to achieve additional energy dissipation. It should be noted that too high a metal content can easily destroy the Hertzian contact between the superelastic ceramic particles, resulting in a reduction in the amount of phase transition. When the particle size of the superelastic ceramic is too small, it is easy to cause the critical stress of the phase transition to be too large, which is not conducive to phase change; when the particle size is too large, the superelastic ceramic mainly exists in the form of polycrystalline, resulting in a specific surface area that is too small, which is not conducive to full contact with the metal.

[0027] In the preparation method of the energy-absorbing metal-ceramic composite particle stack, by further adjusting the particle size ratio of the superelastic ceramic to the metal, the superelastic ceramic can be effectively prevented from being wrapped by the metal particles, thereby ensuring direct and effective contact between the ceramic particles to form a connected three-dimensional skeleton; further selecting solvent dispersion and low ball milling speed can eliminate the influence of mechanical stress on the superelastic ceramic to the greatest extent, while avoiding the breakage of the superelastic ceramic during the ball milling process.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The preparation method adopted by the present invention ensures the structural integrity of the three-dimensional ceramic network stacking and the reversible phase change ability of the ceramic monomer, and realizes the uniform filling of metal particles in the gaps of the ceramic stacking, which can fully transfer stress through the metal gap filling, and is conducive to fully inducing the reversible phase change of the superelastic ceramic.

[0030] 2. The composite particle stacking prepared by the present invention can induce a higher level of reversible phase transition of superelastic ceramics, with high compressive strength, high energy dissipation density and good cycle stability.

[0031] 3. The preparation method adopted by the present invention alleviates the bottleneck problem of the phase transition variable threshold of superelastic ceramics, has a wide range of applications, saves energy and time, and has a reliable and efficient process, which is conducive to the realization of large-scale preparation and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0033] Figure 1 1. A physical picture (left picture) and a structural picture (right picture) of a sleeve die for stacking pre-pressing according to an embodiment of the present invention;

[0034] Figure 2 This is a scanning electron microscope image of the energy-absorbing metal ceramic composite particle stack prepared according to Example 1 of the present invention. The nominal composition of the composite particle stack is 5% Cu@95% Ce 0.16 Zr 0.84 O2;

[0035] Figure 3 This is an X-ray diffraction diagram of the energy-absorbing metal ceramic composite particle stacking prepared according to Example 1 of the present invention. The horizontal axis is the 2θ angle and the vertical axis is the diffraction intensity. The nominal composition of the composite particle stacking is 5% Cu@95% Ce. 0.16 Zr 0.84 O2;

[0036] Figure 4 This is an X-ray diffraction diagram of the energy-absorbing metal ceramic composite particle stack prepared according to Example 1 of the present invention after 50 cycles of loading. The horizontal axis is the 2θ angle and the vertical axis is the diffraction intensity. The nominal composition of the composite particle stack is 5% Cu@95% Ce 0.16 Zr 0.84 O2;

[0037] Figure 5 : is a force versus displacement diagram of the energy-absorbing metal ceramic composite particle stack prepared according to Example 1 of the present invention, wherein the horizontal axis is the uniaxial force applied to the mold, and the vertical axis is the corrected particle stack displacement. The nominal composition of the composite particle stack is 5% Cu@95% Ce 0.16 Zr 0.84 O2;

[0038] Figure 6 : is a graph showing the relationship between the energy dissipation density of the energy-absorbing metal ceramic composite particle stack prepared according to Example 1 of the present invention and the number of cycles, wherein the horizontal axis is the number of cycles and the vertical axis is the energy dissipation density. The nominal composition of the composite particle stack is 5% Cu@95% Ce 0.16 Zr 0.84 O2, compared with the particle accumulation Ce in Comparative Example 1 0.16 Zr 0.84 O2 contrasts. DETAILED DESCRIPTION

[0039] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0040] The metal matrix powders used in the following examples are all commercially available, with a purity higher than 99.9% (mass percentage). 0.135 Zr 0.865 O2、Ce 0.14 Zr 0.86 O2、Ce 0.16 Zr 0.84 O2、Ce 0.18 Zr 0.82 O2) are prepared by the conventional method described in the US20190039959A1 patent: according to the ratio of elements in the superelastic ceramic particles, zirconium oxide and oxide nanoparticles doped with the element Ce are weighed accordingly, and after uniform dispersion, gel injection molding and sintering are performed, and finally crushing and dispersion are performed, and the corresponding superelastic ceramic particles of the required particle size are screened.

[0041] The compressive stress and energy dissipation performance of the energy-absorbing metal ceramic composite particle stack in all embodiments and comparative examples are tested by the test method in GB / T 11106-2022. The specific test method for energy dissipation density is: after a "load-unload-reload" cyclic loading experiment at a set stress amplitude, the original force-displacement curve is obtained; after deducting the background correction curve, the energy dissipation density of each cycle is extracted according to the integral area of ​​the curve. In all embodiments, the austenite content of the composite particle stack in the prepared state and after loading is higher than 85% (mass percentage).

[0042] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0043] Example 1

[0044] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Cu@95% Ce 0.16 Zr 0.84 O2), the specific steps of its preparation are as follows:

[0045] 1) Solvent dispersion: weigh 9.5 g Ce 0.16 Zr 0.84O2 superelastic ceramic particles (particle size of 2 μm) and 0.5 g pure copper particles (particle size of 1 μm); the above two particles were added to 50 ml of ethanol and mixed thoroughly for 12 hours using a ball mill at 150 rpm;

[0046] 2) Drying: The mixed slurry obtained in step 1) is placed in a ventilated environment at 50° C. and dried for 8 hours to obtain metal-ceramic composite particles.

[0047] 3) Stacking pre-pressing: The metal-ceramic composite particles are Figure 1 The sleeve mold shown is preloaded with 200MPa for pre-compression to obtain metal-ceramic composite particle accumulation. The sleeve mold is homemade and made of commercially available C300 alloy steel. It is pre-wired and then solid-solution treated at 830°C for 1 hour, quenched, and aged at 480°C for 12 hours to obtain the final sleeve mold. The sleeve mold includes a push rod, a cushion block 1, a sleeve, a cushion block 2, and a base, which are arranged in sequence from top to bottom; the sleeve is a hollow structure, and the lower end of the push rod and the cushion block can be sleeved on the hollow part of the sleeve (the sizes of each component are well matched, and the specific sizes are detailed in Figure 1 ). During pre-pressing, the metal-ceramic composite particles are loaded into the hollow part of the hollow cylindrical sleeve, and the pads 1 and 2 play the role of sealing the particles. Then, the upper end of the circular push rod is pressed by an external pressure device, and the load is transferred through the pads, and pressed downward into the hollow part of the hollow cylindrical sleeve, thereby achieving pre-pressing of the metal-ceramic composite particles.

[0048] 4) Material characterization: Scanning electron microscopy (SEM) was used to characterize the metal-ceramic composite particles with a stacking ratio of 5% Cu@95% Ce 0.16 Zr 0.84 O2, such as Figure 2 As shown in the figure, fine metal Cu powder is dispersed in the superelastic ceramic Ce 0.16 Zr 0.84 O2 pores. X-ray diffraction (XRD) calibration of the phase composition of the prepared composite particles, such as Figure 3 As shown, the austenite content is 97%. Further, the composite particle stack is placed in a sleeve mold and a cyclic loading experiment is performed with a stress amplitude of 1 GPa. The phase measurement of the composite particle stack after 50 cycles of loading shows that the austenite content is 86%, as shown in FIG. Figure 4 The corrected curve of force and displacement is shown in Figure 5 As shown in Figure 2, the relationship between energy dissipation density and the number of cycles is as follows: Figure 6 As shown. After the 10th cycle, the energy dissipation density is basically stable. After 50 cycles, the energy dissipation density is ~3.6J / cm 3 Finally, the metal-ceramic composite particles (5% Cu@95% Ce 0.16 Zr0.84 The composition and properties of O2 are listed in Table 1.

[0049] Example 2

[0050] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (25% Cu@75% Ce 0.16 Zr 0.84 The specific preparation steps are basically the same as those in Example 1, except that:

[0051] In step 1) of this embodiment, 7.5 g of Ce was weighed. 0.16 Zr 0.84 O2 superelastic ceramic particles (particle size 2μm) and 2.5g pure copper particles (particle size 1μm). The energy dissipation density of the 50th cycle is ~3.0J / cm 3 Finally, the metal-ceramic composite particle stacking (25% Cu@75% Ce 0.16 Zr 0.84 The composition and properties of O2 are listed in Table 1.

[0052] Example 3

[0053] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (15% Cu@85% Ce 0.14 Zr 0.86 The specific preparation steps are basically the same as those in Example 1, except that:

[0054] In step 1) of this embodiment, 8.5 g of Ce was weighed. 0.14 Zr 0.86 O2 superelastic ceramic particles (particle size 10μm) and 1.5g pure copper particles (particle size 5μm). The energy dissipation density of the 50th cycle is ~2.5J / cm 3 Finally, the metal-ceramic composite particle stacking (15% Cu@85% Ce 0.14 Zr 0.86 The composition and properties of O2 are listed in Table 1.

[0055] Example 4

[0056] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (45% Cu@55% Ce 0.18 Zr 0.82 The specific preparation steps are basically the same as those in Example 1, except that:

[0057] In step 1) of this embodiment, 5.5 g of Ce was weighed. 0.18 Zr 0.82O2 superelastic ceramic particles (particle size 7μm) and 4.5g pure copper particles (particle size 2μm). The energy dissipation density of the 50th cycle is ~2.4J / cm 3 Finally, the metal-ceramic composite particles (45% Cu@55% Ce 0.18 Zr 0.82 The composition and properties of O2 are listed in Table 1.

[0058] Example 5

[0059] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Al@95% Ce 0.14 Zr 0.86 O2), the specific steps of its preparation are as follows:

[0060] 1) Solvent dispersion: weigh 9.5 g Ce 0.14 Zr 0.86 O2 superelastic ceramic particles (particle size of 5 μm) and 0.5 g pure aluminum particles (particle size of 1 μm); add the above two particles into 75 ml of propanol and mix them thoroughly in a ball mill at 100 rpm for 8 h;

[0061] 2) Drying: The mixed slurry obtained in step 1) is placed in a ventilated environment at 80° C. and dried for 12 hours to obtain metal-ceramic composite particles.

[0062] 3) Stacking pre-pressing: The metal-ceramic composite particles are Figure 1 The sleeve mold shown is preloaded with 100 MPa for pre-compression to obtain metal-ceramic composite particle accumulation.

[0063] 4) Material characterization: The composite particles were stacked in a sleeve mold and subjected to a cyclic loading test with a stress amplitude of 1 GPa. After the 10th cycle, the energy dissipation density was basically stable. The energy dissipation density of the 50th cycle was ~2.8 J / cm 3 Finally, the metal-ceramic composite particles (5% Al@95% Ce 0.14 Zr 0.86 The composition and properties of O2 are listed in Table 1.

[0064] Example 6

[0065] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (15% Al@85% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those of Example 5, except that:

[0066] In step 1) of this embodiment, 8.5 g of Ce was weighed. 0.16 Zr 0.84O2 superelastic ceramic particles (particle size 2μm) and 1.5g pure aluminum particles (particle size 1μm). The energy dissipation density of the 50th cycle is ~2.6J / cm 3 Finally, the metal-ceramic composite particle stacking (15% Al@85% Ce 0.16 Zr 0.84 The composition and properties of O2 are listed in Table 1.

[0067] Example 7

[0068] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Al@95% Ce 0.14 Zr 0.86 O2), the specific preparation steps are basically the same as those of Example 5, except that:

[0069] In step 1) of this embodiment, 9.5 g of Ce was weighed. 0.14 Zr 0.86 O2 superelastic ceramic particles (particle size 7 μm) and 0.5 g pure aluminum particles (particle size 1 μm). The energy dissipation density of the 50th cycle is ~2.0 J / cm 3 Finally, the metal-ceramic composite particles (5% Al@95% Ce 0.14 Zr 0.86 The composition and properties of O2 are listed in Table 1.

[0070] Example 8

[0071] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Al@95% Ce 0.14 Zr 0.86 O2), the specific preparation steps are basically the same as those of Example 5, except that:

[0072] In step 1) of this embodiment, 9.5 g of Ce was weighed. 0.14 Zr 0.86 O2 superelastic ceramic particles (particle size 1 μm) and 0.5 g pure aluminum particles (particle size 1 μm). The energy dissipation density of the 50th cycle is ~1.8 J / cm 3 Finally, the metal-ceramic composite particles (5% Al@95% Ce 0.14 Zr 0.86 The composition and properties of O2 are listed in Table 1.

[0073] Example 9

[0074] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (20% Ni@80% Ce 0.14 Zr 0.86 O2), the specific steps of its preparation are as follows:

[0075] 1) Solvent dispersion: weigh 8.0 g Ce 0.14 Zr 0.86 O2 superelastic ceramic particles (particle size of 2 μm) and 2.0 g of pure nickel particles (particle size of 0.5 μm); the above two particles were added to 50 ml of ethanol and fully mixed using a ball mill at 100 rpm for 12 hours;

[0076] 2) Drying: The mixed slurry obtained in step 1) is placed in a ventilated environment at 50° C. and dried for 12 hours to obtain metal-ceramic composite particles.

[0077] 3) Stacking pre-pressing: The metal-ceramic composite particles are Figure 1 The sleeve mold shown is preloaded with 200 MPa for pre-compression to obtain metal-ceramic composite particle accumulation.

[0078] 4) Material characterization: The composite particles were stacked in a sleeve mold and subjected to a cyclic loading test with a stress amplitude of 1 GPa. After the 10th cycle, the energy dissipation density was basically stable. The energy dissipation density at the 50th cycle was ~3.8 J / cm 3 Finally, the metal-ceramic composite particle stacking (20% Ni@80% Ce 0.14 Zr 0.86 The composition and properties of O2 are listed in Table 1.

[0079] Example 10

[0080] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Ni@95% Ce 0.16 Zr 0.84 The specific preparation steps are basically the same as those in Example 9, except that:

[0081] In step 1) of this embodiment, 9.5 g of Ce was weighed. 0.16 Zr 0.84 O2 superelastic ceramic particles (particle size 2 μm) and 0.5 g pure nickel particles (particle size 1 μm). The energy dissipation density of the 50th cycle is ~3.1 J / cm 3 Finally, the metal-ceramic composite particles (5% Ni@95% Ce 0.16 Zr 0.84 The composition and properties of O2 are listed in Table 1.

[0082] Embodiment 11

[0083] This embodiment provides an energy-absorbing metal-ceramic composite particle stack (5% Ti@95% Ce 0.16 Zr 0.84The specific preparation steps are basically the same as those in Example 1, except that:

[0084] In step 1) of this embodiment, 9.5 g of Ce was weighed. 0.16 Zr 0.84 O2 superelastic ceramic particles (particle size 3 μm) and 0.5 g pure titanium particles (particle size 1 μm). The energy dissipation density of the 50th cycle is ~2.9 J / cm 3 Finally, the metal-ceramic composite particles (5% Ti@95% Ce 0.16 Zr 0.84 The composition and properties of O2 are listed in Table 1.

[0085] Comparative Example 1

[0086] This comparative example provides a ceramic particle stack (Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those in Example 1, except that pure copper particles are not added in this comparative example. The relationship between the energy dissipation density and the number of cycles is as follows: Figure 6 The components and properties of the superelastic ceramic particle stacking are finally obtained and are listed in Table 1.

[0087] Comparative Example 2

[0088] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (1% Cu@98% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those in Example 1, except that: in this comparative example, 9.9 g of Ce 0.16 Zr 0.84 O2 superelastic ceramic particles and 0.1 g pure copper particles. The components and properties of the metal-ceramic composite particles finally obtained are listed in Table 1.

[0089] Comparative Example 3

[0090] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (50% Cu@50% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those in Example 1, except that: in this comparative example, 5.0 g of Ce 0.16 Zr 0.84 O2 superelastic ceramic particles and 5.0 grams of pure copper particles. The components and properties of the metal-ceramic composite particles finally obtained are listed in Table 1.

[0091] Comparative Example 4

[0092] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (5% Cu@95% Ce 0.135 Zr 0.865 O2), the specific preparation steps are basically the same as those in Example 1, except that: the ceramic particle component selected in this comparative example is Ce 0.135 Zr 0.865 O2 does not have superelasticity. The components and properties of the metal-ceramic composite particle stacking are finally obtained and are listed in Table 1.

[0093] Comparative Example 5

[0094] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (5% Cu@95% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those in Example 1, except that the pure copper particles used in this comparative example have a particle size of 0.2 μm. The components and properties of the metal-ceramic composite particle stack are finally obtained and are listed in Table 1.

[0095] Comparative Example 6

[0096] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (5% Al@95% Ce 0.14 Zr 0.86 O2), the specific preparation steps are basically the same as those in Example 5, except that the pure aluminum particles used in this comparative example have a particle size of 10 μm. The components and properties of the metal-ceramic composite particle stack are listed in Table 1.

[0097] Comparative Example 7

[0098] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (5% Cu@95% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those of Example 1, except that in the solvent dispersion step of this comparative example, no solvent ethanol is added, and dry grinding is performed. The components and properties of the metal-ceramic composite particle stack are finally obtained and are listed in Table 1.

[0099] Comparative Example 8

[0100] This comparative example provides an energy-absorbing metal-ceramic composite particle stack (5% Cu@95% Ce 0.16 Zr 0.84 O2), the specific preparation steps are basically the same as those in Example 1, except that in the solvent dispersion step in this comparative example, the ball mill speed is 300 rpm. The components and properties of the metal-ceramic composite particle stack are finally obtained and are listed in Table 1.

[0101] Table 1 Composition, compressive strength and energy dissipation density of energy-absorbing metal-ceramic composite particle stacking

[0102]

[0103]

[0104] From the comparison of the results of Examples 1 and 2 with Comparative Examples 1, 2 and 3 in Table 1, it can be seen that adding an appropriate amount of metal (5-25%) is beneficial to transferring stress through the metal filled in the gaps of the ceramic skeleton, fully inducing the reversible phase change of the superelastic ceramic, thereby improving the energy dissipation density; excessively high metal content (50%) is likely to destroy the Hertzian contact between the superelastic ceramic particles, resulting in a decrease in the phase change amount, thereby affecting the energy dissipation density.

[0105] From the comparison of the results of Example 1 and Comparative Example 4, it can be seen that the use of ceramics with superelasticity can greatly increase the energy dissipation density of the composite particle stack and make it have superelasticity.

[0106] By comparing the results of Example 1 with Comparative Examples 1 and 5, it can be seen that when the metal particle size is too small (particle size is less than 0.5 μm), the metal cannot effectively fill the ceramic gap and transfer the load, resulting in the energy dissipation density of the composite particle accumulation not being improved compared to Comparative Example 1 when no metal is added.

[0107] From the comparison of the results of Example 5 and Comparative Example 6, it can be seen that when the metal particle size is too large (the particle size is greater than 5 μm), the superelastic ceramic will be wrapped by the metal particles, resulting in the inability to form effective contact between the ceramic particles, destroying the three-dimensional skeleton of the superelastic ceramic, thereby causing a significant decrease in the energy dissipation density of the composite particle stack.

[0108] From the comparison of the results of Example 1 and Comparative Example 7, it can be seen that the use of solvent dispersion can eliminate the influence of mechanical stress on superelastic ceramics to the greatest extent, while dry grinding will lead to an increase in defects of ceramic particles and a partial loss of superelasticity.

[0109] From the comparison of the results of Example 1 and Comparative Example 8, it can be seen that selecting a low ball milling speed can effectively avoid the breakage of the superelastic ceramic during the ball milling process, while a high ball milling speed will lead to a decrease in the energy dissipation density.

[0110] From the comparison of the results of Examples 5, 7 and 8, it can be seen that when the particle size of the superelastic ceramic particles is 1-10 μm, the particle size of the metal particles is 0.5-5 μm, and the particle size ratio of ceramic to metal is 2-5:1, the energy dissipation density of the prepared composite particle stack will be further improved.

[0111] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An energy-absorbing metal-ceramic composite particle stack, characterized in that: The composite particle stack includes superelastic ceramic particles Ce x Zr 1-x O2 and metal particles M, the composition expression is: y%M@(100-y)%Ce x Zr 1-x O2; Wherein, the superelastic ceramic particles Ce x Zr 1-x The particle size of O2 is 1-10 μm; The metal particles M are at least one of Cu, Al, Ti, Ni metal powder or alloy powder thereof, and have a particle size of 0.5-5 μm; In the composition expression, x is the atomic molar ratio, 0.14≤x≤0.18; y is the mass percentage, 5≤y≤45.

2. The energy-absorbing metal-ceramic composite particle stack according to claim 1, characterized in that: In the component expression, 5≤y≤25.

3. The energy-absorbing metal-ceramic composite particle stack according to claim 1, characterized in that: The superelastic ceramic particles Ce x Zr 1-x The particle size ratio of O2 to metal particles M is 2-5:

1.

4. The energy absorbing metal ceramic composite particle stack according to claim 1, characterized in that: The compressive strength of the composite particle stack is above 0.6 GPa.

5. The energy absorbing metal ceramic composite particle stack according to claim 1, characterized in that: After 50 cycles of the composite particle stacking, the energy dissipation density is 1.8 J / cm 3 above.

6. A method for preparing an energy-absorbing metal-ceramic composite particle stack according to any one of claims 1 to 5, characterized in that: The following steps are involved: A1. Solvent dispersion: weigh the superelastic ceramic particles Ce x Zr 1-x O2 and metal particles M are added to a sufficient amount of solvent and mixed thoroughly for 6-18h; A2, drying: placing the mixed slurry obtained in step A1 in a ventilated environment at 50-100° C. and drying for 6-12 hours to obtain metal-ceramic composite particles; A3. Stacking pre-pressing: placing the metal-ceramic composite particles in a mold and pre-pressing them at 100-200 MPa to obtain a stack of metal-ceramic composite particles.

7. The method for preparing the energy-absorbing metal-ceramic composite particle stack according to claim 5, characterized in that: In step A1, the solvent is one of ethanol, propanol, isopropanol, acetone, butanone, or a mixture of several of them.

8. The method for preparing the energy-absorbing metal-ceramic composite particle stack according to claim 5, characterized in that: In step A1, the rotation speed used during the mixing is no more than 150 rpm.

Citation Information

Patent Citations

  • Shape memory ceramic reinforced aluminum-based composite material and preparation method capable of regulating and controlling austenite content

    CN115570132A

  • Inert electrode material in nanocrystalline powder form

    CN1498287A

  • Reinforced magnesium composite and a method of producing thereof

    US20170355020A1

  • Composite particles, composite powder, method for manufacturing composite particles, and method for manufacturing composite member

    US20190016641A1

  • Shape Memory Ceramic Particles and Structures Formed Thereof

    US20190039959A1